2009
DOI: 10.1007/978-3-642-02152-7_27
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Value and Utility Concepts into a Value Decomposition Model for Value-Based Software Engineering

Abstract: Abstract.Value-based software engineering (VBSE) is an emerging stream of research that addresses the value considerations of software and extends the traditional scope of software engineering from technical issues to businessrelevant decision problems. While the concept of value in VBSE relies on the well-established economic value concept, the exact definition for this key concept within VBSE domain is still not well defined or agreed upon. We argue the discourse on value can significantly benefit from drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Several researchers have presented value constructs and corresponding valuation/measurement solutions needed for making decisions about software product development [9][10][11][12][13][14]. However, the contributions are often isolated and have a limited perspective, focusing on, for example, only cost, or only product characteristics like usability.…”
Section: The Absence Of a Consolidated View On Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have presented value constructs and corresponding valuation/measurement solutions needed for making decisions about software product development [9][10][11][12][13][14]. However, the contributions are often isolated and have a limited perspective, focusing on, for example, only cost, or only product characteristics like usability.…”
Section: The Absence Of a Consolidated View On Valuementioning
confidence: 99%
“…Value-based software engineering (VBSE) emphasizes that every decision and/or feature of a product does not have an equal value like in a value-neutral setting [2]. This requires making decisions that are better for overall value creation [8,9], and balancing shortterm and long-term value creation. To enable this, different perspectives and corresponding value constructs need to be considered together while making decisions for sustaining growth and maintaining the competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach that focuses on considering value during the software process is "Value-based Software Engineering" (VBSE) [7]. This approach provides di↵erent elements, such as techniques for determining value by analytical means, and methods for including value considerations into management activities [8,9]. Other related approaches exist, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…These authors identified the factors that determine the decisions about inclusion of certain requirements for implementation. Next, Rönkkö et al [18] present three aspects of software -as a technology, as a design, and as an artifact. They use these aspects to divide the value concept into three components that are relevant for software developing companies and their clients: intrinsic value, externalities and option value.…”
Section: Related Workmentioning
confidence: 99%